Exploring Perceptions Of Productivity and Well-Being Among High-Demand Professionals - Paltarak, Mikita (2025)
This thesis arises from a growing need to address a critical gap in both academic research and professional practice: the lack of a structured understanding of individual productivity strategies in high-demand work environments, such as consulting, investment banking, and technology. While existing literature has focused largely on organizational-level interventions, few studies have explored the personal tools and cognitive habits that enable professionals to sustain their performance over time—especially in roles characterized by long hours, high expectations, and psychological strain. To address this gap, the study first introduces a theory-driven framework that divides personal productivity into three core domains: Effectiveness (task prioritization and decision-making), Efficiency (time management and process optimization), and Occupancy (attention, energy, and cognitive wellness). The framework is developed through an extensive literature review and validated through a two-phase empirical study. A quantitative survey of 105 professionals across high-pressure industries tests whether the consistent application of strategies across these domains correlates with greater productivity, satisfaction, and lower burnout—revealing strong support for this multidimensional model. A complementary qualitative phase deepens this insight, revealing that beyond strategy, mindset plays a pivotal role in sustaining high performance. Interviews uncovered practices such as mental reframing, self-motivation rituals, and value alignment, prompting an extension of the original framework to include Mindset as a fourth pillar of personal productivity. Together, the findings contribute a robust, validated model for understanding how individuals perceive productivity in high-demand jobs—offering both theoretical advancement and practical guidance for those who want to feel more productive. Literature Used: Harung, H. S. (1998).